Proenkephalin A and bioactive adrenomedullin are useful for risk prognostication in cardiac surgery - Hill, Aileen; Bergmann, Deborah; Schulte, Janin; Zayat, Rashad; Marx, Gernot; Simon, Tim-Philipp; Mossanen, Jana; Brücken, Anne; Stoppe, Christian (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Various clinical scores have been developed to predict organ dysfunction and mortality in cardiac surgery patients, but outcome prediction may be inaccurate for some patient groups. Proenkephalin A (penKid) and bioactive Adrenomedullin (bio-ADM) have emerged as promising biomarkers, correlating with shock and organ dysfunction. This imposes the question, if they can be used as prognostic biomarkers for risk stratification in the perioperative setting of cardiac surgery. Methods: Cardiac surgery patients were prospectively enrolled in this observational study. PenKid and bio-ADM plasma levels, as well as markers evaluating inflammation and organ dysfunction were measured at 5 perioperative timepoints from before induction of anesthesia up to 48 hours postoperatively. Clinical data regarding organ dysfunction and patient outcome were recorded during the intensive care unit (ICU)-stay with special focus on acute kidney injury. Results: In 136 cardiac surgery patients the bio-ADM levels increased and penKid levels decreased significantly over time. PenKid was associated with chronic kidney disease, the incidence of acute kidney injury and renal replacement therapy. Bio-ADM was associated with lactate and need for vasopressors. PenKid was useful to predict an ICU-length-of stay >1 day and added prognostic value to the European System for Cardiac Operative Risk Evaluation Score (EuroSCORE) II if measured after the end of cardiopulmonary bypass and 24 hours after cardiac surgery. For bio-ADM the same was true when measured 24 hours after surgery. PenKid also added prognostic value to the EuroSCORE II for the combined outcome “ICU length-of stay >1 day and in-hospital mortality”. Conclusions: The combination of preoperative EuroSCORE II and the intraoperative measurement of penKid may be more useful to predict a prolonged ICU length-of stay and increased mortality than the EuroSCORE II alone. Bio-ADM correlates with markers of shock. More research is encouraged for an early risk stratification, and validation of penKid and bio-ADM as a tool involved in clinical decisions, which may enable early initiation of organ protective strategies.